The Impact of COVID-19 on Contracts and Claims for Infrastructure Projects - Adam, Mona; Mohammed, Amani (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Infrastructure projects have greatly affected the economy of countries, as they have contributed to supporting all economic sectors by providing them with many executive and operational projects. Despite the important role of infrastructure projects in Khartoum State, they are exposed to problems at various stages due to the Covid-19, which led to the failure to complete these stages. This study aimed to identify the extent of the impact of the Covid-19 on infrastructure projects in the Khartoum state and its relationship to claims and construction contracts in terms of costs, time and risks, and who bears and how to distribute the burden of additional costs and losses resulting from this pandemic, and how to contain and overcome the crisis and how to avoid the emergence of conflicts. The survey's descriptive approach was adopted by designing a questionnaire and distributing it to the affected sample. The questionnaire was collected and analyzed using the statistical analysis program and Excel. The results showed revenue losses for the public and private sector by 63.1%, and the Covid-19 also affected infrastructure projects in financial terms by 55%, and the prices of construction materials and direct and indirect costs by 50%, and the cash flow of projects by 49.2%. Based on these results, proposed solutions have been developed to improve the current situation, by standardizing the project cost in dollars to avoid exchange rate hesitation and following FIDIC contracts and formulating it to redress the damage in all sectors, which helps in improving the performance of projects in Khartoum state, which is trying to pass this unprecedented period.